Comparison of WBRT alone, SRS alone, and their combination in the treatment of one or more brain metastases: Review and meta-analysis - Muhammad Khan; Jie Lin; Guixiang Liao; Rong Li; Baiyao Wang; Guozhu Xie; Jieling Zheng; Yawei Yuan (Tumor Biology)
Whole brain radiotherapy has been a standard treatment of brain metastases. Stereotactic radiosurgery provides more focal and aggressive radiation and normal tissue sparing but worse local and distant control. This meta-analysis was performed to assess and compare the effectiveness of whole brain radiotherapy alone, stereotactic radiosurgery alone, and their combination in the treatment of brain metastases based on randomized controlled trial studies. Electronic databases (PubMed, MEDLINE, Embase, and Cochrane Library) were searched to identify randomized controlled trial studies that compared treatment outcome of whole brain radiotherapy and stereotactic radiosurgery. This meta-analysis was performed using the Review Manager (RevMan) software (version 5.2) that is provided by the Cochrane Collaboration. The data used were hazard ratios with 95% confidence intervals calculated for time-to-event data extracted from survival curves and local tumor control rate curves. Odds ratio with 95% confidence intervals were calculated for dichotomous data, while mean differences with 95% confidence intervals were calculated for continuous data. Fixed-effects or random-effects models were adopted according to heterogeneity. Five studies (n = 763) were included in this meta-analysis meeting the inclusion criteria. All the included studies were randomized controlled trials. The sample size ranged from 27 to 331. In total 202 (26%) patients with whole brain radiotherapy alone, 196 (26%) patients receiving stereotactic radiosurgery alone, and 365 (48%) patients were in whole brain radiotherapy plus stereotactic radiosurgery group. No significant survival benefit was observed for any treatment approach; hazard ratio was 1.19 (95% confidence interval: 0.96–1.43, p = 0.12) based on three randomized controlled trials for whole brain radiotherapy only compared to whole brain radiotherapy plus stereotactic radiosurgery and hazard ratio was 1.03 (95% confidence interval: 0.82–1.29, p = 0.81) for stereotactic radiosurgery only compared to combined approach. Local control was best achieved when whole brain radiotherapy was combined with stereotactic radiosurgery. Hazard ratio 2.05 (95% confidence interval: 1.36–3.09, p = 0.0006) and hazard ratio 1.84 (95% confidence interval: 1.26–2.70, p = 0.002) were obtained from comparing whole brain radiotherapy only and stereotactic radiosurgery only to whole brain radiotherapy + stereotactic radiosurgery, respectively. No difference in adverse events for treatment difference; odds ratio 1.16 (95% confidence interval: 0.77–1.76, p = 0.48) and odds ratio 0.92 (95% confidence interval: 0.59–1.42, p = 71) for whole brain radiotherapy + stereotactic radiosurgery versus whole brain radiotherapy only and whole brain radiotherapy + stereotactic radiosurgery versus stereotactic radiosurgery only, respectively. Adding stereotactic radiosurgery to whole brain radiotherapy provides better local control as compared to whole brain radiotherapy only and stereotactic radiosurgery only with no difference in radiation related toxicities.